Pengaruh Kultur Teknis Terhadap Hama Pada Tanaman jeruk (Citrus sinensis) di Desa Lebung Batang, Kecamatan Pangkalan Lampam, Kabupaten Ogan Komering Ilir, Sumatera Selatan: Effects of Cultural Technique on the Pest of Citrus (Citrus sinensis) in Village Lebung Batang, Sub District Pangkalan Lampam, District Ogan Komering Ilir, South Sumatra - Arsi Arsi; Patmiyanti Patmiyanti (J-Plantasimbiosa, 2021)
Citrus (Citrus sinensis L.) is an important agricultural commodity and currently occupying the important place in agroindustry, either as fresh fruit or processed products. On of obstacles in the citrus production is the present of crop damaging insects which has been making farmers confused to control. Most of them do not know how to the species or type of insect infesting their citrus cultivation and also do not know how to control them. The objective of this field study was to know the effects of cultural technique culture on the insect population and their damaging effects on the citrus crops (Citrus sinensis)in District Ogan Komering Ilir, South Sumatra .The method reseacrh was survey method started with the determination of survey location, sample plots, sample crops and observation to collect data on insect population and the intensity of damage made by the insects. The study was conducted in two different citrus cultivations. Data of insect population and damage intensity produced were analysed using T test with significant level 5%. The insect found on citrus trees was Toxoptera citridus, (Hemiptera: Aphididae).